2014
DOI: 10.1097/sle.0b013e31828fa659
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Pelvic Pillow on Learning How to Perform Laparoscopic Low Anterior Resection for Rectal Cancer

Abstract: Maintaining an excellent view of the pelvic surgical field with the pelvic pillow might have an impact on learning laparoscopic LAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Hotta et al reported that the operation time and postoperative start of oral intake were shorter and earlier, respectively, and the pelvic surgical field was better by inserting the pelvic pillow for laparoscopic low anterior resection. 29 In the present study, we demonstrated another important finding that the insertion of a back pillow increased the PLA in all patients with GC and more than half of the patients with small PLA developed large PLA. Moreover, the CT image showed that the kyphosis of the thoracic vertebrae could be decreased by the insertion of the back pillow.…”
Section: Discussionsupporting
confidence: 63%
“…Hotta et al reported that the operation time and postoperative start of oral intake were shorter and earlier, respectively, and the pelvic surgical field was better by inserting the pelvic pillow for laparoscopic low anterior resection. 29 In the present study, we demonstrated another important finding that the insertion of a back pillow increased the PLA in all patients with GC and more than half of the patients with small PLA developed large PLA. Moreover, the CT image showed that the kyphosis of the thoracic vertebrae could be decreased by the insertion of the back pillow.…”
Section: Discussionsupporting
confidence: 63%